METHOD OF STUDY OF A STRESSED-DEFORMED STATE OF A SIGNIFICANT ENVIRONMENT IN STATISTICAL AND DYNAMIC VIBRATION ACTION - Svidersky, A. T. (Техніка будівництва, 2020)
It is shown in this paper that loose loam and clay loose soils have significant damping effect, which makes it difficult to determine the true values of elastic modulus using only traditional methods. The determination of elastic modulus in this case is due to the need for excitation in soils of high-frequency oscillations.